Los Mercado (Mercado family): a Family of Aldermen and Wine Harvesters from Aranda de Duero - Cuesta Nieto, José Antonio (Cuadernos de Historia Moderna, 2015)
Diego de Medina Mercado, native of Zamora, settled in Aranda de Duero after getting married to Constanza de Quemada. This way, he connected with the elite families of the town, aldermen and wine harvesters, since the vineyards were the reason of their fortunes. Bernardino de Mercado was his elder son and a clergyman. He was in charge of promoting the family, so he founded a patronage and an entailed state for his brother Josephe de Mercado. As his father, he was alderman of the town and enjoyed a great heritage of free goods.